Pavements from the Point of View of Future Requirements of Road Transport - Corej, Jan; Decky, Martin (Communications - Scientific letters of the University of Zilina, 1999)
Pavement is a very important part of road construction. The authors of this paper deal with problems which are to be solved not only at present but also in the future. They are mainly the following questions: improvement of functional properties of pavement surface, suitable construction parts, computing methods and quality of different pavement layers.